Silicon nanoparticles for use as negative electrode active material in secondary batteries and method for producing same

The dry and wet pulverization of polysilicon fine powder addresses impurity issues in silicon nanoparticles, enhancing battery performance by producing high-purity nanoparticles with controlled size, thus improving initial discharge capacity and lifespan.

JP2024545899AActive Publication Date: 2024-12-13OCI CO LTD(KR)
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
JP2024538133
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2021-12-30
Filing Date
2022-12-21
Publication Date
2024-12-13
Estimated Expiration
2042-12-21

AI Technical Summary

Technical Problem

Existing methods for producing silicon nanoparticles for secondary battery negative electrodes face challenges such as high impurity content, particularly metals and oxygen, leading to structural destruction and reduced battery performance due to volumetric expansion during charging and discharging.

Method used

A method involving dry and wet pulverization of polysilicon fine powder to produce silicon nanoparticles with controlled particle size and low impurity content, using specific grinding equipment and solvents to minimize metal and oxygen contamination.

Benefits of technology

The production method results in high-purity silicon nanoparticles with controlled particle size, improving initial discharge capacity, efficiency, and life characteristics of secondary batteries.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024545899000001_ABST
    Figure 2024545899000001_ABST
Patent Text Reader

Abstract

The present invention relates to an efficient method for producing silicon nanoparticles with controlled particle size while minimizing the content of impurities such as metals and oxygen. Specifically, the present invention relates to a method for producing silicon nanoparticles with a particle size of 80 nm or less by using fine polysilicon powder as a raw material. <D 50 <150nm and 100nm <D 90 A method for producing silicon nanoparticles having a particle size of <250 nm, a total metal impurity content of 200 ppm or less, and a total oxygen content of 10.0% or less can be provided.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to silicon nanoparticles for use as an anode active material in a secondary battery, which can improve the initial discharge capacity (IDC), initial efficiency (ICE) and life characteristics of the secondary battery, and a method for manufacturing the same. [Background technology]

[0002] The improvement of secondary battery performance is based on the components of the positive electrode material, the negative electrode material, and the electrolyte.

[0003] Among the above components, graphite-based materials, which are mainly used as the negative electrode active material of negative electrode materials, have excellent electrochemical performance and are in common commercial use due to their low price. However, their theoretical capacity is limited to 370 mAh / g, which limits their application to high-capacity secondary batteries.

[0004] To overcome the above limitations, non-graphite anode materials such as silicon, tin, and germanium have emerged as alternative materials, of which silicon has a theoretical capacity of 4000~4200mAh / g, which is about 10 times higher than graphite, and is therefore attracting attention as a material that can replace graphite. However, compared to its high theoretical capacity, silicon experiences a large volume expansion of about 400% during charging and discharging, which can cause structural destruction of the material and shorten its lifespan.

[0005] As a method for mitigating the volume expansion of silicon, a method has been developed in which a carbon material is mixed to produce a composite material, and it is known to use silicon nanoparticles as the silicon material.

[0006] In order to exhibit excellent quality as a negative electrode active material so as to improve battery performance when applied to secondary batteries, silicon nanoparticles need to have low impurity contents such as metals and oxygen, and to have controlled particle size.

[0007] For this reason, silicon nanoparticles have been produced using various silicon raw materials, but problems still remain, such as the low purity of the silicon raw materials themselves, high raw material and processing costs, and the tendency for impurities to flow in during processing.

[0008] Specifically, when metal silicon (MG-Si) is used as the silicon raw material, it has a high impurity content, and it is difficult to significantly reduce the impurity content even through the crushing process. Therefore, when metal silicon is made into nanoparticles and applied to secondary batteries, side reactions may occur during the charging and discharging of the battery, which ultimately has a negative effect on the performance of the battery.

[0009] In addition, when silicon kerf generated during slicing of silicon ingots is used as a raw material, the raw material itself may be highly pure, but there is a drawback in the process that it is easily contaminated by the lubricating oil and water used during the slicing process. Silicon oxidizes when it comes into contact with water, so when this is used as a raw material, the oxygen and impurity content increases, which may cause a decrease in battery performance when applied to secondary batteries.

[0010] In addition, when using polysilicon chunks or chips, the initial particle size is too large, which increases the number of grinding steps, increasing the grinding time and cost, and is inefficient and unsuitable for mass production due to its high price compared to other raw materials.

[0011] Therefore, it is necessary to develop a method for efficiently manufacturing and producing silicon nanoparticles with controlled particle size while solving the above problems and minimizing the content of impurities such as metals and oxygen. Summary of the Invention [Problem to be solved by the invention]

[0012] It is an object of the present invention to provide an efficient method for producing silicon nanoparticles of controlled size while minimizing the content of impurities such as metals and oxygen.

[0013] Another object of the present invention is to provide a negative electrode active material for a secondary battery prepared by the above-mentioned method, and a negative electrode material for a secondary battery and a secondary battery including the same, so that the initial discharge capacity, initial efficiency, and life characteristics of the secondary battery can be improved.

[0014] The object of the present invention is not limited to the object mentioned above, and other objects and advantages of the present invention not mentioned can be understood from the following description and can be more clearly understood from the embodiments of the present invention. Also, the object and advantages of the present invention can be realized and understood by the means and combinations thereof as set forth in the claims. [Means for solving the problem]

[0015] According to one aspect of the present invention, the method includes the steps of dry-milling a polysilicon fine powder; and wet-milling the dry-milled polysilicon fine powder; and the polysilicon fine powder has a size of 0.2 mm or less. <D 50 <0.4mm and 0.5mm <D 90 The silicon nanoparticles have a particle size of 80 nm or less and a total metal impurity content of 500 ppm or less. <D 50 <150nm and 100nm <D 90 A method for producing silicon nanoparticles having a particle size of <250 nm and a total metal impurity content of 200 ppm or less can be provided.

[0016] According to another aspect of the present invention, <D 50 <150nm and 100nm <D 90 Silicon nanoparticles can be provided having a particle size of <250 nm, a total metal impurity content of 200 ppm or less, and a total oxygen content of 10.0% or less.

[0017] According to yet another aspect of the present invention, it is possible to provide a negative electrode material for a secondary battery, which contains the negative electrode active material for a secondary battery, and a secondary battery. Effect of the Invention

[0018] According to the method for producing silicon nanoparticles of the present invention, since polysilicon fine powder having a relatively low raw material cost and a low content of metal impurities is used as a raw material, the process cost can be reduced and silicon nanoparticles can be efficiently produced.

[0019] According to the method for producing silicon nanoparticles of the present invention, <D 50 <150nm and 100nm <D 90 High purity and high quality silicon nanoparticles can be produced having a particle size of <250 nm, a total metal impurity content of 200 ppm or less, and a total oxygen content of 10.0% or less.

[0020] By applying the silicon nanoparticles produced according to the method for producing silicon nanoparticles according to the present invention as a negative electrode active material for a secondary battery, the initial discharge capacity, initial efficiency and life characteristics of the secondary battery can be improved.

[0021] The above-mentioned effects and specific effects of the present invention will be described in conjunction with the following description of the preferred embodiment of the invention. [Brief description of the drawings]

[0022] [Figure 1] FIG. 1 is a graph showing floating initial charge efficiency (ICE; discharge amount relative to initial charge amount) and initial discharge capacity (IDC; initial discharge capacity) in a half-cell test using silicon nanoparticles according to Example 1, Comparative Example 1, and Comparative Example 2 of the present invention. [Diagram 2]FIG. 1 is a graph showing a capacity retention rate in a half-cell test in which silicon nanoparticles according to Example 1 of the present invention, Comparative Example 1, and Comparative Example 2 are applied. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0023] The above-mentioned objects, features and advantages will be described in detail below with reference to the accompanying drawings, so that a person having ordinary skill in the art to which the present invention pertains can easily implement the technical idea of ​​the present invention. In describing the present invention, if a detailed description of a known technology according to the present invention is deemed to make the gist of the present invention unclear, the detailed description will be omitted. Hereinafter, a preferred embodiment of the present invention will be described in detail with reference to the accompanying drawings. The same reference numerals in the drawings are used to indicate the same or similar components.

[0024] Of the contents not described in this specification, explanations of those that can be sufficiently inferred from a technical standpoint by a person of ordinary skill in this technical field will be omitted.

[0025] In this specification, the "metal of the metal impurities" refers to a metal element that affects the quality when silicon nanoparticles are used as a negative electrode active material of a secondary battery, and typically refers to the 24 metal elements Al to Zn listed in Tables 2 and 3 of this specification, but is not necessarily limited thereto.

[0026] In the following, when an arbitrary structure is arranged on the "top (or bottom)" of a component or "above (or below)" a component, it means that the arbitrary structure is not only arranged in contact with the upper surface (or lower surface) of the component, but also that other structures may be interposed between the component and the arbitrary structure arranged on (or below) the component.

[0027] Also, when it is described that a certain component is "connected", "coupled", or "joined" to another component, it should be understood that the above components may be directly connected or joined to each other, but other components may "intervene" between the components, or each component may be "connected", "coupled", or "joined" through other components.

[0028] As used herein, "<X" and "≦X" mean less than X and less than or equal to X, respectively, and ">X" and "≧X" mean greater than X and greater than or equal to X, respectively.

[0029] In this specification, the size of balls and beads means "diameter".

[0030] Hereinafter, the method for producing silicon nanoparticles according to the present invention will be described in detail.

[0031] The present invention uses polysilicon fine powder as a raw material for silicon nanoparticles. However, since polysilicon fine powder is a raw material with relatively low demand, it has a low price, a very low impurity content, and when used as an active material for secondary batteries, the performance of the secondary batteries can be improved.

[0032] Specifically, the present invention selects polysilicon fine powder having a particle size of 0.2 mm < D 50 < 0.4 mm and 0.5 mm < D 90 < 1 mm and having a total metal impurity content of 500 ppm or less as a raw material. By pulverizing these raw materials of polysilicon fine powder, preferably, 80 nm < D 50 < 150 nm and 100 nm < D 90 < 250 nm, more preferably, 100 nm < D 50 < 120 nm and 120 nm < D 90 < 200 nm and having a total metal impurity content of 200 ppm or less, silicon nanoparticles can be produced.

[0033] The grinding of the polysilicon powder can be divided into dry grinding and wet grinding. By grinding, the size of the silicon particles should be gradually reduced. The grinding device is not particularly limited, and any device commonly used in the industry can be used.

[0034] For example, the dry milling can be carried out in one type of apparatus selected from the group consisting of a ball mill apparatus, a jet mill apparatus, and a disk mill apparatus, and is preferably carried out in a ball mill apparatus.

[0035] When dry grinding is carried out in a ball mill, the balls of the ball mill may be selected to have a size of approximately 10 to 50 mm, more preferably 10 to 30 mm, and even more preferably 20 to 25 mm.

[0036] In addition, when selecting a ball mill device for dry grinding, the material of the balls used may be a ceramic material, a metal material, a ceramic-metal mixed material, etc., and is not particularly limited, but it is preferable not to use a material containing metal impurities as a main component as listed in Tables 2 and 3 of this specification. In addition, it is more preferable to select a material having properties such as hardness and density that can show excellent grinding performance in the grinding process, and as a specific example, zirconia balls containing zirconium (Zr) can be used.

[0037] The wet grinding can be performed in two stages, a primary wet grinding and a secondary wet grinding. For example, the wet grinding can be performed in a bead mill. After the primary wet grinding, the secondary wet grinding is performed to reduce the particle size of the silicon nanoparticles to 80 nm. <D 50 <150nm and 100nm <D 90 Can be adjusted to meet <250nm.

[0038] For example, both the primary wet grinding and the secondary wet grinding can be carried out in a bead mill device, and in this case, it is preferable to select beads, which are the second beads used in the secondary wet grinding, having an average size smaller than that of the first beads used in the primary wet grinding.

[0039] Specifically, the average size of the first beads may be, for example, 0.2 to 5 mm, for example, 0.3 to 1 mm, or for example, 0.3 to 0.5 mm, and the average size of the second beads may be, for example, 0.05 to 0.5 mm, for example, 0.1 to 0.3 mm, or for example, 0.1 to 0.2 mm, but are not limited thereto, and the average size of the first beads must be selected to be larger than the average size of the second beads.

[0040] In addition, when selecting a bead mill device for wet grinding, the material of the beads used is not particularly limited, and may be a ceramic material, a metal material, a ceramic-metal mixed material, etc., but it is preferable not to use a material containing as a main component the metal impurities listed in Tables 2 and 3 of this specification. In addition, it is more preferable to select a material having properties such as hardness and density that can show excellent grinding performance in the grinding process, and as a specific example, zirconia beads containing zirconium (Zr) can be used.

[0041] In this way, a solvent is used when wet grinding is performed. In this case, an alcohol-based solvent can be used, for example, an alcohol-based solvent such as ethanol, propanol, or methanol.

[0042] In addition, in order to increase the degree of dispersion of silicon and prevent oxidation of silicon, an additive can be used together with a solvent when wet grinding, for example, stearic acid can be used as the additive. Preferably, the stearic acid as an additive is dissolved in a solvent before starting wet grinding, and then stirred together with silicon to increase the degree of dispersion while mixing.

[0043] By carrying out wet or dry milling, the impurity content can be even higher since it is common for the material to be contaminated by substances such as lubricants used in the cutting equipment and solvents such as water used in wet milling, and in particular the oxygen content can be increased by silicon oxidation.

[0044] If the oxygen content of silicon nanoparticles is increased, it may cause a decrease in the performance of the secondary battery when used as an anode active material for the secondary battery. Therefore, it is important to adjust the total oxygen content of silicon nanoparticles to be low, which is a different characteristic from the impurity metal content and is required for high-quality, high-purity silicon nanoparticles that should be satisfied separately regardless of the particle size adjustment of the silicon nanoparticles. Therefore, it is preferable that the total oxygen content of the silicon nanoparticles finally produced is 10.0% or less.

[0045] In this way, silicon nanoparticles produced according to the silicon nanoparticle production method of the present invention may have high purity and precisely controlled particle size, and therefore may have the effect of improving initial discharge capacity, initial efficiency, and life characteristics when applied to secondary batteries. EXAMPLES

[0046] The configuration and operation of the present invention will be described in more detail below with reference to preferred embodiments of the present invention, which are presented as preferred examples of the present invention and are not to be construed as limiting the present invention in any sense.

[0047] 1. Preparation of Silicon Nanoparticles Polysilicon fine powder (OCI, ST900) was used as the raw material in Example 1, metal silicon (MG-Si) was used as the raw material in Comparative Example 1, and silicon kerf was used as the raw material in Comparative Example 2. Dry grinding was performed in a ball mill using zirconia balls, and wet grinding was performed in a bead mill using zirconia beads to produce silicon nanoparticles.

[0048] The initial particle sizes and final particle sizes of the raw materials in Example 1, Comparative Example 1, and Comparative Example 2 and the grinding conditions (ball or bead size and grinding time) are as shown in Table 1 below.

[0049] [Table 1]

[0050] As shown in Table 1 above, in order to make the experiments comparable, the final particle sizes after grinding were adjusted to be as similar as possible, and since the initial particle sizes of the raw materials were different, the grinding processes were different.

[0051] In the wet grinding step, 100 parts by weight (600 g) of the raw material was mixed with 400 parts by weight (2400 g) of ethanol and 20 parts by weight (120 g) of stearic acid.

[0052] The metal contents of the silicon raw materials (before grinding) in Example 1 and Comparative Examples 1 and 2 are shown in Table 2 below, and the metal impurity contents and oxygen contents of the silicon nanoparticles (after grinding; in a slurry state) are shown in Table 3 below. At this time, the metal impurity contents were measured using Thermo Fisher's "iCAP 7600" equipment, and the oxygen contents were measured using LECO's "ONH836" equipment.

[0053] [Table 2]

[0054] [Table 3]

[0055] As can be seen from Tables 2 and 3 above, the silicon nanoparticles of Example 1 had a significantly lower content of impurity metal elements than the silicon nanoparticles of Comparative Examples 1 and 2.

[0056] Furthermore, in Example 1, although wet pulverization was carried out twice, the oxygen content was lower than in Comparative Examples 1 and 2 in which wet pulverization was carried out once or twice, and the total oxygen content in Example 1 satisfied the requirement of 10% or less.

[0057] 2. Half-Cell Test (1) Manufacturing of silicon-carbon composites Silicon-carbon composites were produced using the silicon nanoparticle slurries produced in Example 1, Comparative Example 1, and Comparative Example 2, respectively, and pitch (HSPP with a softening point of 240°C; OCI Co.), and the specific method is as follows.

[0058] 4.5g of pitch was completely dissolved in 200ml of THF (tetrahydrofuran), and 40g of crushed silicon nanoparticle slurry was added and stirred for more than 1 hour. After that, it was dried using an evaporator, and the dried powder was put into a muffle furnace and heat-treated at 1000℃ under a nitrogen gas atmosphere to produce a silicon-carbon composite.

[0059] (2) Manufacturing of half cells To analyze the electrochemical properties of the negative electrode material for secondary batteries, a negative electrode plate was fabricated using a powder mixture of 10% by weight of silicon-carbon composite and 90% by weight of artificial graphite as the negative active material. The negative electrode plate was fabricated by casting a slurry of the active material, conductive material (Super-P, Imerys Graphite & Carbon), and binder in a weight ratio of 94:1:5 onto copper foil. The binder used was a mixture of CMC and SBR in a weight ratio of 3:7. The fabricated negative electrode plate was fabricated into a coin cell using Li metal as the counter electrode to confirm the electrochemical properties.

[0060] (3) Measurement method and conditions for half-cell test The charge and discharge conditions were charge CC / CV: 0.01V / 0.01C, discharge CC 1.5V, and the rate limiting was 0.2C.

[0061] Using a half-cell device TOSCAT-3100, the initial charge efficiency (ICE; discharge amount relative to initial charge amount), initial charge capacity (ICC; initial charge capacity), and initial discharge capacity (IDC; initial discharge capacity) were measured and shown in Table 4 below, and a graph showing floating ICE and IDC is shown in Figure 1. In addition, the lifespan at 40 cycles was measured, and a graph showing the capacity retention rate is shown in Figure 2 (horizontal axis: number of cycles, vertical axis: specific discharge capacity).

[0062] [Table 4]

[0063] As can be seen from Table 4, Figures 1 and 2 above, when the silicon nanoparticles of Example 1 were applied, it was found that the initial charge capacity (ICC), initial discharge capacity (IDC), initial efficiency (ICE), etc. were superior in all aspects to those of Comparative Examples 1 and 2, which used other raw materials (MG-Si, Si kerf), and the capacity retention rate was also improved.

[0064] Although the present invention has been described above with reference to the illustrative drawings, the present invention is not limited to the embodiments and drawings disclosed in this specification, and it is obvious that various modifications can be made by those skilled in the art within the scope of the technical concept of the present invention. Furthermore, even if the effects of the configuration of the present invention are not explicitly described and explained while describing the embodiments of the present invention, it is natural that the effects that can be predicted by the configuration should also be recognized.

Claims

1. dry-milling the polysilicon fine powder; and wet-grinding the dry-milled polysilicon fine powder; Including, The polysilicon fine powder has a diameter of 0.2 mm<D 50 <0.4 mm and 0.5 mm <D 90 having a particle size of <1 mm and a total metal impurity content of 500 ppm or less; The silicon nanoparticles are 80 nm < D 50 < 150 nm and 100 nm < D 90 having a particle size of <250 nm and a total metal impurity content of 200 ppm or less; A method for producing silicon nanoparticles.

2. The total oxygen content of the silicon nanoparticles is 10.0% or less; The method for producing silicon nanoparticles according to claim 1 .

3. The dry grinding is carried out in one type of apparatus selected from the group consisting of a ball mill apparatus, a jet mill apparatus, and a disk mill apparatus. The method for producing silicon nanoparticles according to claim 1 .

4. The wet grinding is divided into a primary wet grinding and a secondary wet grinding, and is performed in a bead mill device. The first wet grinding and the second wet grinding are performed using first beads and second beads having different sizes, and the average size of the second beads is smaller than the average size of the first beads. The method for producing silicon nanoparticles according to claim 1 .

5. The wet grinding is carried out by adding an alcohol-based solvent. The method for producing silicon nanoparticles according to claim 1 .

6. Add stearic acid to the alcohol solvent; The method for producing silicon nanoparticles according to claim 5 .

7. Produced according to the method for producing silicon nanoparticles according to any one of claims 1 to 6. Silicon nanoparticles.

8. The silicon nanoparticles according to claim 7 are included. Negative electrode active material for secondary batteries.

9. The negative electrode active material for a secondary battery comprising the silicon nanoparticles according to claim 7, Negative electrode material for secondary batteries.

10. The negative electrode active material for a secondary battery comprising the silicon nanoparticles according to claim 7, Secondary battery.

Citation Information

Patent Citations

  • Rapid generation of nanoparticles from bulk solids at room temperature

    JP2007515361A

  • Silicon / germanium nanoparticle inks, doped particles, printing methods, and processes for semiconductor applications

    JP2010514585A

  • Positive electrode active material for secondary battery and method for producing same

    JP2019532459A

  • Silicon based anode material for lithium secondary battery with controlled NANO size particles, lithium secondary battery having the same, and method for preparing the same

    KR1020160059121A

  • The method for fabrication of silicon nano particle

    KR102280900B1